Prevalence of Dental Erosion among Children aged 11-12 years Old in Primary Schools at Sammawa City(South of Iraq) - Shayma Abdullah Hanoon (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objective: The purpose of this research was to assess the prevalence of dental erosion in children betweenthe ages of 11 and 12 years and compare the various factors influencing dental erosion in both study andcontrol groups.Materials and Methods: a clinical assessment of the research was performed among children aged 11- 12years to assess the prevalence of dental erosion in relation to various factors that may cause erosion. Thesample size was 102 children with diagnosed dental erosion(63 boys and39 girls) and saliva from thesechildren was collected using a questionnaire to study the various factors that correlate with dental erosion.Results: the children examined were 1000 aged between 11and 12 years. The prevalence was 10.2 per centmore than girls (3.9per cent) with the highest level in boys(6.3per cent). The salivary flow rate and saliva PHwere lower in the study group compared to the control group and lower in boys compared to girls in the samegroup. Tooth brushing frequencies and carbonated drink intake exhibited a greater effect on the developmentof erosion in study group compared with the control group.Conclusion: in Sammawa city, the prevalence of dental erosion was low and in boys more than girls, andin study group, the salivary flow rate and saliva PH was low. The severity of dental erosion increases withincreased intake of carbonated beverages and tooth brushing frequencies.